Emerging non-antibody‒drug conjugates (non-ADCs) therapeutics of toxins for cancer treatment - Xiaolan Xu; Jiaming Zhang; Tao Wang; Jing Li; Yukang Rong; Yanfang Wang; Chenxia Bai; Qing Yan; Xiaohua Ran; Yingli Wang; Tianhong Zhang; Jin Sun; et al. (Elsevier, 2024)
The non-selective cytotoxicity of toxins limits the clinical relevance of the toxins. In recent years, toxins have been widely used as warheads for antibody‒drug conjugates (ADCs) due to their efficient killing activity against various cancer cells. Although ADCs confer certain targeting properties to the toxins, low drug loading capacity, possible immunogenicity, and other drawbacks also limit the potential application of ADCs. Recently, non-ADC delivery strategies for toxins have been extensively investigated. To further understand the application of toxins in anti-tumor, this paper provided an overview of prodrugs, nanodrug delivery systems, and biomimetic drug delivery systems. In addition, toxins and their combination strategies with other therapies were discussed. Finally, the prospect and challenge of toxins in cancer treatment were also summarized.